Efektivitas Bimbingan Karir Dalam Mendukung Program Vokasi di Provinsi Riau - Syartiwidya, Syartiwidya; Sari Mutiara, Candra; Cahyani, T. Marlina (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2024)
This research aims to (1) determine the implementation of a career guidance program for students regarding the competencies needed to enter the world of work; (2) analyze the contribution of career guidance programs for vocational school students in order to develop themselves in appropriate career achievements. The method used in this research is quantitative, namely a cross-sectional design, while the qualitative method uses a deep interview and observation approach. The subject in this research are the students of SMKN 3, SMKN 7, SMKN Pertanian dan SMK Muhammadiyah I. The research results show that Career Guidance has a correlation or contribution to students' interest and readiness to enter the world of work. Students who have interest and work readiness and feel the benefits of Career Guidance are dominated by women. Research recommendations are (1) Curriculum alignment is needed; project-based learning; as well as Educators or instructors from industry, business and the world of work (DUDI); (2) It is necessary to increase teacher internship time as well as internship/field work practice for students at DUDI; (3) Career Guidance needs to be further optimized by developing a Career Guidance module that is appropriate to current developments and DUDI needs.